1987
DOI: 10.1161/01.atv.7.4.408
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of human intermediate and very low density lipoprotein subfractions from normal and dysbetalipoproteinemic plasma. In vivo studies in rat.

Abstract: Subtractions of radlolodinated d < 1.019 g/ml llpoproteins were Isolated by nonequillbrlum density gradient ultracentrlfugatlon (DGU) from normal and dysbetalipoproteinemic human plasma and were Injected into rats. Size and density (d) of lipoprotein products formed over 8 hours were assessed by gradient gel electrophoresis and equilibrium DGU, respectively. Subtractions containing a subspecies of very low density lipoprotelns (VLDL) of particle diameter > 350 A were cleared rapidly from the plasma and formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
1

Year Published

1988
1988
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
0
16
0
1
Order By: Relevance
“…However, the metabolic determinants of these parallel pathways are not understood. Studies in our laboratory have focused on the role of IDL heterogeneity in metabolic pathways leading to discrete LDL subspecies (1,2,68). The results have indicated that the small VLDL-2/IDL-1 particle spectrum includes precursors of mid-sized LDL-II, while IDL-2, which overlaps the size and density distribution of large LDL (LDL-I), also includes metabolic precursors of these particles (Fig.…”
Section: Metabolic Influences On Ldl Heterogeneitymentioning
confidence: 99%
“…However, the metabolic determinants of these parallel pathways are not understood. Studies in our laboratory have focused on the role of IDL heterogeneity in metabolic pathways leading to discrete LDL subspecies (1,2,68). The results have indicated that the small VLDL-2/IDL-1 particle spectrum includes precursors of mid-sized LDL-II, while IDL-2, which overlaps the size and density distribution of large LDL (LDL-I), also includes metabolic precursors of these particles (Fig.…”
Section: Metabolic Influences On Ldl Heterogeneitymentioning
confidence: 99%
“…This transfer process is probably accomplished in an early phase of LDL formation, such as the VLDL or IDL phase, so that we cannot confirm the presence of the pathway for the smaller LDL in normal controls. Krauss 19 and Musliner et al 20 have reported multiple precursor-product relations involving individual VLDL, IDL, and LDL subpopulations and have suggested the existence of dual pathways for the production of IDL and LDL subspecies. They demonstrated the existence of two sizes of subpopulations in both VLDL and DDL, but only one in LDL, of normal human plasma.…”
Section: Smentioning
confidence: 99%
“…Apolipoprotein B (apoB) containing lipoproteins comprise multiple subclasses differing in size, density, and chemical composition (1)(2)(3)(4)(5)(6)(7)(8). The size distribution of these subclasses is commonly analyzed by non-denaturing GGE using stains for protein (Coomassie Brilliant Blue) or lipids (Sudan black, Oil Red O).…”
Section: Supplementary Abstract Fluorophor • Ldl • Apolipoprotein B mentioning
confidence: 99%